Validity of two rapid point of care influenza tests and direct fluorescence assay in comparison of real time PCR for swine of origin influenza virus - S.M. Al Johani; M. Al Balwi; B. Al Alwan; R. Al Hefdhi; A. Hajeer (Elsevier, 2011)
Background: A novel swine origin influenza virus (S-OIV) is continue to spread worldwide and a global declaration of 2009 influenza pandemic was made by World Health Organization (WHO) June 2009, this along with approaching the winter season at the northern hemisphere, increase the interest to provide a quick, easy, affordable and available point of care testing for S-OIV. Objectives: To determine the performance of two rapid point-of-care (POC) tests for influenza virus as well as direct fluorescence assay for the detection of the recently emerged a novel swine origin influenza virus (S-OIV). Study design: A total of 143 respiratory samples which was submitted to Pathology and Laboratory Medicine at King AbdulAziz Medical City in Riyadh, Saudi Arabia from June 6th 2009 till June 28th 2009. All samples were tested in parallel using two rapid assays (BD Directigen EZ Flu®) and (TruFlu, Meridian®) as well as (Imagen Flu A/B DFA, Oxoid®) and compare it with RT-PCR. Each test's performed by different team, who were blinded for other team's result. Data gathered and we analyzed the analytical validity of each test. Results: The analytical sensitivity of the two influenza antigen detection tests for S-OIV was very low in comparison with RT-PCR, BD Directigen EZ performance was better than TruFlu test with sensitivities of 20.6% and 9.7% respectively. DFA perform much better than POC tests with sensitivity of 32.35%, specificity of 99.08% and PPV, NPV of 90% and 81.20% respectively. Conclusion: The analytical sensitivity of the selected influenza A antigen detection tests for detection of S-OIV was very low, and should not be used to exclude S-OIV, DFA may be used as first line test especially during after hours or weekends, but negative results must confirmed by RT-PCR. Keywords: Rapid influenza diagnostics, DFA, RT-PCR, H1N1